Oxidized phospholipids modify plasminogen and apolipoprotein(a): Implications for vascular disease - Scanu, Angelo M.; Stafforini, Diana M.; Edelstein, Celina (Scientific Research Publishing, 2012)
Whereas the close structural homology between human plasminogen and apolipoprotein(a) has been known for a number of years only recent studies have revealed that both proteins carry linked oxidized phospholipids that may modify the function of these proteins. Future studies should provide a better understanding of oxidized phospholipid adducts and the role played by lipoprotein-associated phospholipase A2 for which cleavage specificity has been established when these modified lipids are in a free form.
Keywords: Plasminogen; Apolipoprotein(a); Lipoprotein(a); Oxidized Phospholipids; Oxidized Phosphatidylcholines